Composite Materials with Enhanced Conductivities. Issue 7 (29th February 2016) - Zhu, Hanxing; Fan, Tongxiang; Zhang, Di
Abstract : The authors have analyzed the isotropic thermal/electrical conductivities of two types of specially structured composite materials. Closed‐form results have been obtained for predicting the conductivities of the composites, and the accuracy has been verified by FE simulations. The obtained results in this paper are compared to the relevant theoretical predictions and experimental measurements. It has been demonstrated that the type‐I composites have achieved a conductivity that is almost the same as the highest possible theoretical upper limit, and the type‐II composites have a conductivity significantly greater than the experimental results of conventional isotropic composite materials. Abstract : Closed‐form results for the isotropic conductivities of two types of specially structured two‐phase composites are obtained in this paper . It is found that the type‐I composites can achieve the maximum possible theoretical upper limit for isotropic conductivity and the type‐II composites have a conductivity significantly greater than the conventional particle or fiber composites.